IN VITRO WOUND HEALING AND ANTIMICROBIAL PROPERTY OF COTTON FABRICS COATED OPTIMIZED SILVER NANOPARTICLES SYNTHESIZED USING PELTOPHORUM PTEROCARPUM LEAF EXTRACTS - ANNAMALAI P,; BALASHANMUGAM P,; KALAICHELVAN PT, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was aimed to study at investigating the antibacterial potential of silver nanoparticles (AgNPs) coated cotton fabrics against different pathogens and also for their wound healing property using fibroblasts cells. Materials and Methods: The leaf extracts of Peltophorum pterocarpum were used for the synthesis of AgNPs and were characterizing using ultraviolet-visible spectrophotometer, transmission electron microscopy, energy dispersive X-ray (EDX) spectroscopy, dynamic light scattering analysis, and zeta potential measurement. The AgNPs were coated on cotton fabrics and tested for their antibacterial efficacy using agar well diffusion method. The wound healing property of synthesized AgNPs was tested using fibroblast 3T3 cells. Results: The plant extracts of P. pterocarpum were utilized for AgNPs. The optimum condition for synthesizing AgNPs was found to be 1 mg/ml plant concentration, 7 pH, 1 mM silver nitrate concatenation, and incubation temperature of 37°C. The shape of synthesized AgNPs was found to be spherical with an average size between 20 and 50 nm, and elemental silver peaks were confirmed by EDX spectrum. The cotton fabrics coated with AgNPs show good zone of inhibition against all the tested pathogens and the treated fabrics were also characterized using scanning electron microscope which reveals the presence of AgNPs on the fabrics. The scratch assay reveals that the AgNPs have good wound healing activity when tested against fibroblast 3T3. Conclusion: The present results conclude that the synthesized AgNPs have good stability with potent antimicrobial activity when coated with cotton fabrics. The AgNPs also found to have good activity significant wound healing activity when tested using fibroblast cells.